Analysis of Early Childhood Social Development Achievement Levels - Aerani, Aerani; Haliza, Siti; Muslihanah, Muslihanah; Hafizatulumah, Hafizatulumah; Zaeniah, Zaeniah; Dewi, Denda Cindera; Harmayanti, Windi Ayu; Sahid, Lintia Purnama; Suryani, Irma (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of writing this article is to understand the developmental process in early childhood. Writing this article uses the literature method, namely collecting reading sources from previous journals to find out actions in social development in early childhood. The results of this article were obtained from sources from journals covering early childhood social issues as well as social behavior which includes actions such as: sharing, cooperation, helping, donations, honesty. Where this social behavior is very influential in the social development of children, especially early childhood. The characteristics of early childhood social development include the ability to interact, children are able to share and take turns, and children have a sense of empathy.